Role of the apparent diffusion coefficient measurement by diffusion weighted magnetic resonance imaging in the diagnosis of Fasciola hepatica in the liver - Onur, Mehmet Ruhi; Cicekci, Mehtap; Kayali, Alperen; Kocakoc, Ercan; Aygun, Cem (Springer, 2011)
Purpose. The aim of this study was to investigate the diagnostic role of the apparent diffusion coefficient (ADC) measurement in the diagnosis of focal parenchymal lesions and to understand the discriminating role of the ADC value for differentiating Fasciola lesions from other focal liver lesions. Materials and methods. We measured ADC values of parenchymal lesions and liver parenchyma in 18 patients with Fasciola hepatica infestation at b 100, b 600, and b 1000 s/mm(2) gradients. We further measured average ADC values of hepatic metastases (n = 21), hepatocellular carcinomas (n = 21), cholangiocarcinomas (n = 7), hydatid cysts (n = 12), and focal nodular hyperplasia (FNH) (n = 12) and compared them with average ADC values for Fasciola hepatica. Results. The differences between average ADC values of lesions (2.16 +/- 0.36 x 10(-3) mm(2)/s) and parenchyma (1.64 +/- 0.2 x 10(-3) mm(2)/s) at three gradients were statistically signifi cant (P < 0.05). Mean ADC values of Fasciola hepatica lesions were significantly different from most of the other focal hepatic lesions, except FNH at all gradients and hydatid cyst at only the b 100 gradient. Conclusion. ADC measurement may be a complementary method in the diagnosis of Fasciola hepatica, and it may be used to differentiate these lesions from other focal liver lesions.
Keywords: Fascioliasis; Liver; Magnetic resonance imaging; Apparent diffusion coefficient